Utility of 3-Month Surveillance F-18 FDG PET/CT in Surgically Resected Oral Squamous Cell Carcinoma. (March 2018) - Marquardt, Michael; Anderson, Carryn; Ginader, Timothy; Parkhurst, Jessica; Pagedar, Nitin; Bayon, Rodrigo; Clamon, Gerald; Hoover, Andrew; Buatti, John
Objectives: To evaluate the performance of surveillance F-18 fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) 1 year after imaging in oral squamous cell carcinoma (OSCC) patients treated with definitive surgery and adjuvant (chemo)radiotherapy (RT). Methods and Materials: Surveillance PET/CT accuracy was retrospectively evaluated in OSCC patients receiving surgical resection and (chemo)RT. Pathologic risk factors were assessed for influence on accuracy of the post-RT PET/CT. Results: Fifty-four patients with median follow-up of 3.8 years met inclusion criteria. A PET/CT obtained a median of 3.4 months after RT revealed 11 (20.4%) instances of true disease recurrence: 4 locoregional alone, 6 distant alone, and 1 patient with locoregional and distant disease. Locoregional detection sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 55.6%, 75.0%, 33.3%, and 88.2%, respectively. For distant recurrence, the respective values were 100%, 95.2%, 77.8%, and 100%. Absence of bone invasion, absence of pT4 disease, and disease within the tongue were independently associated with higher sensitivity ( P = .048). Perineural invasion was associated with increased specificity ( P = .027), and tumor location in the tongue was associated with a higher PPV ( P = .007) on surveillance PET/CT. Conclusions: Post-RT PET/CT accuracy information for surgically managed OSCC patients demonstrates significant associations with pathologic factors.